Molecular detection of Leptospira spp. in small wild rodents from rural areas of São Paulo State, Brazil - da Silva, Evelyn Cristine [UNESP]; Fornazari, Felipe [UNESP]; de Paula Antunes, João Marcelo Azevedo; de Castro Demoner, Larissa; de Oliveira, Lucia Helena O’Dwyer [UNESP]; Peres, Marina Gea; Megid, Jane [UNESP]; Langoni, Helio [UNESP] (My University, 2023)
Background: Leptospirosis represents a One Health issue, affecting humans and animals. This study investigated pathogenic leptospires in small wild rodents in São Paulo, Brazil. Methods: Kidney samples from 164 rodents underwent qPCR testing, targeting pathogenic Leptospira spp. Results: Thirty-five animals (21.34%) tested positive, including five rodent species: Akodon montensis (2/21; 9.5%), Necromys lasiurus (1/4; 25%), Oligoryzomys nigripes (24/92; 26.1%), Oligoryzomys flavescens (5/26; 19.2%), and Sooretamys angouya (3/14; 21.4%). Botucatu municipality exhibited the highest prevalence, with 42.5% (20/47) of the animals testing positive. Conclusions: The presence of Leptospira spp. in wild rodents suggests they may be chronic carriers, contaminating the environment.
Keywords: leptospirosis; qPCR; Renal carrier; Wildlife